2004
DOI: 10.1001/archinte.164.22.2483
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Usefulness of D-Dimer Depending on Clinical Probability and Cutoff Value in Outpatients With Suspected Pulmonary Embolism

Abstract: The safety of D-dimer testing in patients with a high clinical probability of PE is not established, and testing results are rarely negative in such patients. Increasing the enzyme-linked immunosorbent assay D-dimer cutoff value only marginally increased the test's usefulness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(59 citation statements)
references
References 30 publications
1
51
0
7
Order By: Relevance
“…11,12 We believed that the cutoff Linkins et al proposed for low PTP patients (more than four times the standard cutoff, based on ROC curve analysis) would represent a sharp change from current practice, so we decided by consensus to test the effect of a simple doubling the threshold low PTP patients. This adjustment would have allowed the NPV of the quantitative D-dimer to remain 99%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 We believed that the cutoff Linkins et al proposed for low PTP patients (more than four times the standard cutoff, based on ROC curve analysis) would represent a sharp change from current practice, so we decided by consensus to test the effect of a simple doubling the threshold low PTP patients. This adjustment would have allowed the NPV of the quantitative D-dimer to remain 99%.…”
Section: Discussionmentioning
confidence: 99%
“…This adjustment strategy was evaluated by Linkins et al, 11 who showed in a retrospective analysis that adjusting the D-dimer's threshold could increase the D-dimer's specificity to 60% without compromising sensitivity (95%), or negative predictive value (NPV; >98%). 11 A similar strategy was also analyzed retrospectively by Righini et al, 12 who demonstrated a marginal increase in the D-dimer's usefulness.…”
Section: Q Uantitative D-dimer Testing Is Commonly Used To Rule Out Amentioning
confidence: 99%
“…We identifi ed 19 studies that evaluated clinical prediction rules for the diagnosis of DVT, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and 8 studies evaluating clinical prediction rules for the diagnosis of pulmonary embolism, [35][36][37][38][39][40][41][42] although common patients were reported in 3 studies. [40][41][42] (Supplemental Appendix 1, available online at http://www.annfammed.org/cgi/content/full/5/1/63/DC1). The quality of the studies was fairly high, because all patients had an appropriate reference standard, the study sample was well described, and there was no verifi cation bias.…”
Section: Are Clinical Prediction Rules Valuable For Diagnosing Dvt Ormentioning
confidence: 99%
“…35,37,38 In the 2 studies that evaluated the Geneva rule (Table 2), the prevalence of pulmonary embolism in the high pretest probability stratum was 77% to 85%. 41,42 Those in the moderate pretest probability stratum had a prevalence of 34% to 35%, and those in the low pretest probability stratum had a prevalence of 7%. These 2 studies included common patients.…”
Section: Diagnosis O F DV T a Nd Pementioning
confidence: 99%
“…Не требуется измерения D димера и у больных с высокой клини ческой вероятностью ТЭЛА в связи с низким отри цательным прогностическим значением этого мето да в данной популяции [202]. Показатель D димера также неинформативен у госпитализированных, т. к. для получения клинически значимых отри цательных результатов требуется обследовае очень большого числа больных (number needed to test).…”
Section: предполагаемая тэла без шока и гипотензииunclassified